Evaluation of Possible Genotoxic Activity of Dirithromycin in Cultured Human Lymphocytes - Ahmet Kayraldız; Lale Dönbak; Ayşe Yavuz Kocaman; Esra Köker; Şule Gökçe (Journal of Toxicology)
Dirithromycin antibiotic is a 14-membered lactone ring macrolide and is widely used in medicine to treat many different types of bacterial infections. In the present study, the possible genotoxicity of dirithromycin was evaluated in cultured human lymphocytes by using sister chromatid exchanges (SCEs), chromosome aberration (CA), and micronucleus (MN) tests and also cell proliferation kinetics such as mitotic index (MI), replication index (RI), and nuclear division index (NDI) were analyzed for cytotoxicity. Cell cultures were treated with four different concentrations of dirithromycin (37.75, 67.50, 125, and 250 µg/mL) for 24 and 48 h periods. Dirithromycin significantly induced SCE and MN frequency at all concentrations in both 24 and 48 h treated cells. In addition, CA level has been markedly increased in the cells treated with almost all concentrations of dirithromycin for 24 (except 37.75 µg/mL) and 48 h treatment periods as compared to control. However, MI, RI, and NDI values were not affected by the dirithromycin treatment (p > 0.05). The results of this study indicated that dirithromycin treatment caused genetic damage by increasing the level of cytogenetic endpoints, suggesting its genotoxic and mutagenic action on human lymphocytes in vitro.